The Use of Task in Vocabulary Lessons and the Lexical Learning of Low English Proficiency Level Students in Indonesia - Wullur, Bill Glenny (8ISC Abstract Proceedings, 2022)
The experimental study investigates the effectiveness of the use of tasks in vocabulary lessons toward lexical language learning. Lexical learning was determined using a comparison of vocabulary test results pre-test and post-test the task-based instruction. The participants were 72 Indonesian university freshmen of different but generally low proficiency levels who completed 12 tasks over a six-week period. They were paired in all-male, male-female, and female-female dyads. Parametric statistical t-test analysis was used to examine the difference between pretest and post-test results. The findings indicated that lexical learning occurred and was maintained over time. In the case of lexical learning, this study suggests that female students learned and maintained the new words better than their male counterparts and that the differences in proficiency levels prior to the task were maintained after task lessons. The item analysis showed that the majority of the target words were learned, but some were learned better than others. Acquisition of the most highly learned words was also maintained over time. There are implications from the findings of this research toward EFL lessons and program management. Using a task-based lesson was found effective for facilitating lexical learning and, therefore, the use of tasks should be encouraged in EFL lessons more generally. Keywords : EFL lessons, vocabulary lessons, lexical learning, task-based